EFEKTIVITAS SENAM CERIA UNTUK MENINGKATKAN KEMAMPUAN MOTORIK KASAR ANAK TUNAGRAHITA RINGAN - Cicha Yumaika; Ardisal Ardisal (Dinasti Research, 2020)
limitations of mildly impaired children in gross motor skills is one of the problems that is often encountered in children with mild mental retardation, so educators need to have a variety of efforts and new information in helping to improve gross motor skills in children with intellectual disabilities. One way that can be done by educators is to do rhythmic movements that is cheerful gymnastics. the purpose of this study was to determine the greatness of use cheerful gymnastic movements to improve the gross motor manipulative skills of mentally retardation children with mild V grade children in SLB XI Pauh Padang. This type of research is pre-test and post-test, with pre-eksperimen research with one group design. Participants in this study were five mild retarded children who sat in class V SLB. This study used the instrument as a test Cheerful Gymnastics steps test to measure the gross motor skills of a child in doing cheerful gymnastic movements. The data can be proven using the Wilcoxon, with Statical Product and service Solution (SPSS) 22. The finish results obtained indicate that Cheerful Gymnastics is effective in increasing the gross motor skills or abilities of five mentally retarded children in SLB Muhamadiyah IX Pauh Padang.